Evaluation of The Effect of Pasak Bumi (Eurycoma longifolia Jack) to Increase Androgen Levels - Pratomo, Hurip (International Series on Interdisciplinary Science and Technology, 2016)
Abstract—Background:The ability of reproductive disorders in men and experimental male rat is characterized among other things by a decrease in androgen such as testosterone levels. Materials of pasak bumi root (Eurycoma longifolia Jack) increased libido behavior of experimental male rat. Libido associated with higher levels of testosterone, it is therefore necessary to evaluate the effect of pasak bumi on androgen levels such as testosterone. Methods: Male rats at 9.00 am treated controls and pasak bumi, then at 14.00 pm tempted with estrus female rats 10 minutes. Then, both control and pasak bumi blood samples were collected from male rat heart on day 1st and day 3rd at 14.15 pm. Measurement of testosterone levels were calculated using radioimmunoassay (RIA). Results: An increase in serum testosterone levels in the blood on day-3rd administration pasak bumi boiled water 18 mg/200 g dose significantly different than the control within day 1st to 3rd. The average levels of testosterone administration control (boiled water of aquades) day 1st = 0.50 ng/ml, day 3rd = 2.46 ng / ml, increased markedly on pasak bumi treatment day 1st = 4.00 ng / ml and day 3 = 9.73 ng / ml, (Duncan test, α=0.05). Conclusions: Testosterone levels can be increased markedly after the consumption of the pasak bumi boiled water for 3 days. Keywords—Pasak bumi, a dose of 18 mg/200 g, testosterone.